2018
DOI: 10.1136/bmjopen-2017-020230
|View full text |Cite
|
Sign up to set email alerts
|

Now you see me: a pragmatic cohort study comparing first and final radiological diagnoses in the emergency department

Abstract: ObjectivesTo (1) compare timely but preliminary and definitive but delayed radiological reports in a large urban level 1 trauma centre, (2) assess the clinical significance of their differences and (3) identify clinical predictors of such differences.Design, setting and participantsWe performed a retrospective record review for all 2914 patients who presented to our university affiliated emergency department (ED) during a 6-week period. In those that underwent radiological imaging, we compared the patients’ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…A previous retrospective record review in internal medicine [15] and a review of diagnostic error in primary care [66] found similar associations. Previous studies also found patient age [6769], gender [66, 68], or chief complaint [42, 44, 61, 62] to be associated with diagnostic error, others, [67] including ours, did not.…”
Section: Discussionsupporting
confidence: 64%
“…A previous retrospective record review in internal medicine [15] and a review of diagnostic error in primary care [66] found similar associations. Previous studies also found patient age [6769], gender [66, 68], or chief complaint [42, 44, 61, 62] to be associated with diagnostic error, others, [67] including ours, did not.…”
Section: Discussionsupporting
confidence: 64%
“…The study thus compares the EDs radiology based diagnoses to a gold standard. When compared to this gold standard of a certified radiologist, one third of the differences identified were judged clinically relevant by two independent expert raters [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also noted that EPs have the benefit of making a diagnosis on clinical grounds rather than just a static image and, therefore, the EP treatment may have been appropriate 7. In a 2018 study performed in Switzerland the authors examined discrepancies in interpretations for various imaging modalities, and in subgroup analysis of radiographs they found a discrepancy rate of 17.9% with a clinically significant disagreement rate of 5.67% 13…”
Section: Discussionmentioning
confidence: 99%